2003
DOI: 10.1007/s00468-002-0226-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential impacts of long-term (CO2) and O3 exposure on growth of northern conifer and deciduous tree species

Abstract: The long-term effects of elevated CO 2 and CO 2 +O 3 concentrations on the growth allocation in northern provenances of Norway spruce [Picea abies (L.) Karst.], Scots pine [Pinus sylvestris (L.)] and pubescent birch clones (Betula pubescens Ehrh.) were examined in open-top chambers after a 4-year-long experiment. The total biomass responses of the tree seedlings to increased CO 2 and CO 2 +O 3 concentrations were not statistically significant and varied between the provenances and species. The seedlings of nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The treeline ecotone is considered in many respects a harsh environment (Körner, 1998), such that the lack of responsiveness to CO 2 by Pinus , the more classic of the two treeline genera in our study and which is arguably not carbon limited according to a global comparison of treeline Pinus (Hoch & Körner, 2003), would fit this interpretation. Vanhatalo et al (2003) also found less responsiveness in the northern (more harsh environment) of two provenances of 10‐year‐old P. sylvestris in their 4‐year OTC study in Finland. In the only other long term in situ test of elevated CO 2 concentrations in harsh high mountain conditions (a Carex sward at 2500 m a.s.l.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The treeline ecotone is considered in many respects a harsh environment (Körner, 1998), such that the lack of responsiveness to CO 2 by Pinus , the more classic of the two treeline genera in our study and which is arguably not carbon limited according to a global comparison of treeline Pinus (Hoch & Körner, 2003), would fit this interpretation. Vanhatalo et al (2003) also found less responsiveness in the northern (more harsh environment) of two provenances of 10‐year‐old P. sylvestris in their 4‐year OTC study in Finland. In the only other long term in situ test of elevated CO 2 concentrations in harsh high mountain conditions (a Carex sward at 2500 m a.s.l.…”
Section: Discussionmentioning
confidence: 95%
“…Studies in which conifers showed a clear ring width or biomass response to elevated CO 2 treatment, like we observe after four years in L. decidua, include a 4-year OTC experiment of P. taeda seedlings growing under nonlimiting nutrient conditions (Telewski et al, 1999), as well as a 4-year study starting with 13-year-old P. taeda growing on old fields (Hamilton et al, 2002), a 3-year OTC study starting with 3-year-old P. sylvestris (Ceulemans et al, 2002) and a 4-year phytotron study starting with 1-year-old P. sylvestris (Ziche & Overdieck, 2004), both growing in unamended but fertile soils, and a 4-year model ecosystem study starting with 2-to 3year-old Picea abies grown in natural forest soils of low and high fertility (Spinnler et al, 2002). In contrast, conifer studies showing no significant response to CO 2 enrichment, like we observe in P. uncinata, include a 4-year OTC study starting with 2-year-old Pseudotsuga menziesii under low nutrients (Olszyk et al, 2005), a 3-year model ecosystem study of 4-year-old P. abies under low and high nutrients (Hättenschwiler et al, 1996), a 4-year OTC study of varying provenances of P. sylvestris and P. abies seedlings under nonlimiting nutrient conditions (Vanhatalo et al, 2003) and two phytotron studies on Larix species, L. sibirica and L. kampferi seedlings, under low and high fertility (Yazaki et al, 2001(Yazaki et al, , 2004. Four further studies where no overall significant growth response to elevated CO 2 is reported (although singular year effects or marginal effects were observed) include a 3-year OTC study of tissue cultured P. radiata seedlings under low and high nutrients where a significant effect was observed under high nutrients in the first year only (Atwell et al, 2003), a 6-year OTC study of P. ponderosa seedlings under varying N levels where an increase in biomass was also observed in the first year only (Johnson et al, 2006), a 3-year OTC study of 15-year-old P. sylvestris under low nutrients where although no significant effect was reported due to large variance, a doubling of radial growth was observed (Kilpeläinen et al, 2003), and a 3-year whole tree chamber study of 41-year-old P. abies where significantly wider rings were only observed in the second year of a 3-year experiment under low nutrient treatment (Kostiainen et al, 2004).…”
Section: Species-specific Co 2 Responsementioning
confidence: 89%
“…In addition, the predicted rise in the temperature and CO 2 levels can lead to significant growth stimulation on properly fertilised plantations, although the magnitude of this increment will depend strongly on various and confounding factors (Weih 2004): i.e. the performance of the varieties used (Vanhatalo et al 2003) and possible pest diseases. In addition, significant yield improvements can be expected in the next years, beyond the scope of the projections presented.…”
Section: Discussionmentioning
confidence: 99%
“…7. For commercial forestry this would mean that slow-growing trees may respond li le to elevated CO 2 (e.g., Vanhatalo et al 2003), while fast-growing trees would possibly do so more strongly (Calfapietra et al 2003;Liberloo et al 2005;Wi ig et al 2005). T he previous analysis was made on the basis of no land use change and in response to climate-induced changes in rainfall through a dynamic (LPJmL) vegetation model.…”
Section: Notesmentioning
confidence: 99%